2021
DOI: 10.1039/d0na00479k
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of impurities on the particle size and optical emission of carbon dots

Abstract: Carbon dots (CDs) are fluorescent nanoparticles that exhibit strong photoluminescence (PL) emission throughout the visible range of the electromagnetic spectrum. Recent studies highlight the presence of fluorescent impurities in CDs...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…[142] They also observed the gradual growth of non-dialyzed CDs upon storage over 13 weeks concomitantly with their quantum yield plummeting from 30 % to 3 %, against no growth at all for dialyzed-CDs. [142] Yellow PL is attributed to CDs surface states while blue PL is attributed to free molecular fluorophores capable of aggregating themselves around CDs upon storage.…”
Section: The Molecular Questionmentioning
confidence: 91%
See 1 more Smart Citation
“…[142] They also observed the gradual growth of non-dialyzed CDs upon storage over 13 weeks concomitantly with their quantum yield plummeting from 30 % to 3 %, against no growth at all for dialyzed-CDs. [142] Yellow PL is attributed to CDs surface states while blue PL is attributed to free molecular fluorophores capable of aggregating themselves around CDs upon storage.…”
Section: The Molecular Questionmentioning
confidence: 91%
“…To illustrate the criticalness of purification, N. Javed and D. M. O'Carroll reported a single blue PL band for their non‐dialyzed CDs, and both blue and yellow bands for dialyzed ones [142] . They also observed the gradual growth of non‐dialyzed CDs upon storage over 13 weeks concomitantly with their quantum yield plummeting from 30 % to 3 %, against no growth at all for dialyzed‐CDs [142] . Yellow PL is attributed to CDs surface states while blue PL is attributed to free molecular fluorophores capable of aggregating themselves around CDs upon storage.…”
Section: Carbon Dots Terminologymentioning
confidence: 99%
“…To identify the material luminescence properties like photoluminescence, chemiluminescence, and phosphorescence, the lifetime measurements are performed using PL lifetime spectroscopy ( Sun et al., 2020 ). The first approximation for the particle size measurements have been achieved using dynamic light scattering ( Javed and O’Carroll, 2021 ) based particle size analyzers, where the Brownian motion of the nanoparticles scatters the laser light and the analysis of the fluctuations is interpreted. Surface charge of the carbon dots has been obtained from zeta potential studies.…”
Section: Characterizationmentioning
confidence: 99%
“…Furthermore, we have recently shown that if CDs are not properly purified, their photoluminescence QY can considerably decrease even when they are stored in the dark. [77] More reports about the photostability of CDs are summarized in Table 1. It is noted that in almost all studies that report significant photobleaching, CDs were derived from bottomup approaches.…”
Section: Photobleachingmentioning
confidence: 99%
“…Furthermore, we have recently shown that if CDs are not properly purified, their photoluminescence QY can considerably decrease even when they are stored in the dark. [ 77 ]…”
Section: Stabilitymentioning
confidence: 99%